A Total systems study Old Swiss Inn - Ben, Rolly D.; Dolor, Katherine Z.; Leyble, Edmundo R.; Mancenido, Michelle V. (Diliman, Quezon City College of Engineering, 2003)
The Old Swiss Inn-Manila has been in the restaurant business since 1946. Since then, it has established a long-standing reputation of providing its upper-crust clienteles with high-class service and sumptuous mouth-watering Swiss cuisine. With businesses and trade industries building or moving to Makati and Ortigas, Manila has been reduced to a historically-rich city which primarily abounds in public structures and landmarks. Without doubt, the sudden shift from being the center of business has had its negative effects to Old Swiss Inn. Sales data from the past 5 years indicate growth during the early part, leveling off, however, in 2000-2002. The trend indicates that the business is already in the maturity stage, which is projected to last somewhere between 6-7 years. This long time "hold-off" from business decline will be primarily due to the loyal set of clients maintained by the Old Swiss Inn ? Manila and the fact that the business is starting to refocus its efforts to the catering business. For the past 5 years, sales from the catering business averaged 57%, with sales from the restaurant averaging only 32%. The strategy of keeping the restaurant while increasing marketing and operational efforts in catering does not come for free. This is evident in the results of the cost analysis done by the team. Return on Sales has declined from 10.33% in 1998 to 1.22% in 2002. Food costs of the restaurant business are increasing, from 37% in 198 to 42% in 2001. The reverse can be said for the catering business, where food costs are declining from 25.12% in 1998 to 21.61% in 2011. Utilities and labor costs comprise 11% and 20% of gross sales, respectively. The cost analysis reaches to one conclusion: the restaurant is being operated inefficiently. Recommendations are based on the following general plans of action for the next 3 years: The first plan of action is supported by brilliant and innovative marketing and promotional schemes. The second plan of action mainly relies on strategies for operational improvement. Should all recommended strategies fall into place, the ROS is expected to increase to 10% on the 3rd year. Sales are projected to increase to P 15 million and P 8 million for the catering and restaurant businesses, respectively, in the same planning horizon.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Old Swiss Inn-Manila.; Food industry and trade; Food service; System design